2008
DOI: 10.1007/s11199-008-9425-3
|View full text |Cite
|
Sign up to set email alerts
|

Questioning Gender and Sexual Identity: Dynamic Links Over Time

Abstract: Dichotomous models of gender have been criticized for failing to represent the experiences of individuals who claim neither an unambiguously female nor male identity. In this paper we argue that the feminist theoretical framework of intersectionality provides a generative approach for interpreting these experiences of gender multiplicity. We review our previous research on four young sexual-minority (i.e., nonheterosexual) women who are participants in a 10-year longitudinal study of sexual identity developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(181 citation statements)
references
References 29 publications
7
167
1
6
Order By: Relevance
“…I have so far only addressed gender and sex and will now briefly introduce my sexuality. Gender and gender identity operate as a basis for sexual attraction (Diamond and Butterworth 2008) and orientation (Tate, 2012) and may help ground the gender discriminatory practices of some (Wood andEagly, 2009. See Tate andYoussef, 2014 for a discussion about these interconnections).…”
Section: A Brief History Of Some Labelsmentioning
confidence: 99%
“…I have so far only addressed gender and sex and will now briefly introduce my sexuality. Gender and gender identity operate as a basis for sexual attraction (Diamond and Butterworth 2008) and orientation (Tate, 2012) and may help ground the gender discriminatory practices of some (Wood andEagly, 2009. See Tate andYoussef, 2014 for a discussion about these interconnections).…”
Section: A Brief History Of Some Labelsmentioning
confidence: 99%
“…In others, some distress may remain, resulting in a life-long search for new adaptations. In again others, the behaviors may be an expression of persisting gender variant identities, but not necessarily complete cross-gender identities (e.g., Diamond & Butterworth, 2008;Lee, 2001). …”
Section: Similarities and Differences Between The Terms Transsexualismentioning
confidence: 99%
“…In the discussion on homosexuality (of individuals without GID), the stability or instability of sexual orientation has been a matter of debate. Recently, prospective studies in non-transsexual samples of women suggest that there is considerable fluidity in sexual orientation, especially for women (Diamond, 2000;Diamond & Butterworth, 2008). In the 1990s, the question arose if the preferences for the gender of sex partners would also change in the course of hormonal and surgical treatment (e.g., Daskalos, 1998;Lawrence, 1999Lawrence, , 2005.…”
Section: Specifiersmentioning
confidence: 99%
“…As we noted in our article, studies have shown considerable fluidity in the development and expression of sexual behavior and orientation over time, particularly in young women (Diamond, 2005(Diamond, , 2007(Diamond, , 2008Diamond & Butterworth, 2008). The current comparison of 17-year-olds in the 6th and 7th cycles of the NSFG suggests that further exploration of factors that may be contributing to changing patterns of same-sex sexual behavior in American adolescents is warranted.…”
mentioning
confidence: 64%